Legal Protection Of Children As Perpetrators Of Criminal Acts In The Indonesian Juvenile Justice System - Muhammad Riduan; Syaiful Asmi Hasibuan (LAWYER: Jurnal Hukum, 2023)
Child protection is an important thing that must be done by the state and society. The forms of child protection are carried out from all aspects, starting from guidance to the family, social control of children's socialization and proper handling through regulations made by the State. Juvenile offenses are crimes committed by children. Juvenile crime can be associated with the term "Juvenile Deliquency", which in Indonesian is known by various terms, namely child delinquency, juvenile delinquency, youth delinquency, stray cadets, or child jalin quersi. Etymologically, it can be explained that "Juvenile" means "child" while "Deliquency" means "crime". Thus "Juvenile Deliquency" is "Child Crime", while when it comes to the subject or the perpetrator, then "Juvenile Deliquency" means child criminals or bad children. The research method used in this writing is the normative juridical method carried out through literature studies that examine secondary data in the form of laws and regulations related to the child punishment system, and child protection laws as well as research results, and other references. This research uses normative legal research because of the provisions regarding sanctions against children in conflict with the law. Child Crimes. Environmental factors contribute greatly to crimes committed by children. The environment of children as victims of criminal acts of decency can also be said that children's crimes are caused by the community environment.